Membaca Liquid Society dari Perspektif Burnout Society - Kuntag, Paulina; Ohoitimur, Johanis (Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
This article synthesizes the ideas of Bauman and Byung-Chul Han regarding the social transformation of modern society. Bauman posits that postmodern society exists in a state of constant flux, leading to the creation of what he terms as a